Optimization of dissolution and fermentation acid production of rhamnolipid-alkali-heat synergistic pretreatment of sludge. (November 2022) - Hao, Shu; Yuling, Liu; Penghe, Zhao; Yang, Jia
Abstract: With the development of the urban sewage treatment industry, the sludge output has increased year by year, and it has the characteristics of large output and high organic content, and has great potential for resource recovery. However, the biodegradability of sludge is poor, resulting in low added value of resource products. Therefore, it is necessary to treat sludge efficiently and improve the utilization. Based on this, the effects on sludge characteristics and acid-producing fermentation were investigated, and optimal conditions were determined by response surface method. The results showed that: The optimal conditions for experimental optimization are rhamnolipid (RL: 40 mg/gVS) alkali (Alk: 35 mg/gVS), heat: 80 °C. Response surface design optimization results are RL (28.44 mg/gVS), NaOH (35 mg/gVS), heat: 80 °C. In the process of RL-Alk-Heat pretreatment, the organic matter dissolution is Heat > Alk. Also, RL, Alk and Heat all promoted the content of fluorescent substances. From the results of the optimal combination verification test, it showed that SC (Soluble carbohydrate) and SP (Soluble protein) increase. Among them, three-factor treatment is higher than two-factor treatment than single-factor treatment. Graphical abstract: Image 1 Highlights: Simulate sludge organic matter and optimize process conditions. In the dissolution of organic matter, the effect of temperature is greater than that of alkali. Under optimal conditions: SCOD dissolution: 5657.88 mg/L, rate: 20.02%. RL, alkali and heat can promote sludge disintegration. RL, alkali and heat can promote acid production by sludge fermentation.